Struktur Pewarisan Dalam Hukum Perdata Serta Analisis Terhadap Kedudukan dan Hak Para Ahli Waris - Gia Anggiani (Advances In Education Journal, 2025)
Inheritance is a fundamental element of civil law because it directly relates to the transfer of the rights and responsibilities of a deceased person to their heirs. The succession process in Indonesian civil law is comprehensively regulated in the Civil Code (KUHPerdata), encompassing inheritance established by law and inheritance based on a will. This study aims to evaluate the inheritance structure in civil law, focusing on the position and rights of heirs. The methodology employed is a normative juridical approach through a review of legislation and concepts. The findings of the discussion indicate that the position of heirs is determined based on blood ties and marriage, then divided into several categories with varying inheritance rights. In addition, the rights of heirs also include the right to inheritance, the right to claim inheritance shares, and legal protection in the event of a dispute. Therefore, a detailed understanding of the inheritance structure and the position of heirs is crucial to ensure legal certainty and justice in the inheritance distribution process.